The Effect of Audit Committee Gender, Audit Committee Size, Audit Opinion, Solvency, and Profitability on Audit Delay - Tiara Puspa Dewi (Majapahit Journal of Islamic Finance and Management, 2025)
This research investigates how audit committee gender, audit committee size, audit opinion, solvency, and profitability influence audit delay in industrial sector companies listed on the IDX in 2021-2023. This quantitative study employed secondary data derived from the annual financial statements of 150 companies. These samples were chosen using purposive sampling and the data was subsequently analyzed with multiple linear regression. The findings indicate a simultaneous significant effect of audit committee gender, audit committee size, audit opinion, solvency, and profitability on audit delay. Breaking this down, audit opinion and profitability negatively affect audit delay, meaning they are associated with shorter delays. In contrast, solvency positively affects audit delay, suggesting it's linked to longer delays. However, audit committee gender and size showed no partial effect on audit delay.